Syawir as Increasing Students' Understanding of Fiqh in Dormitory H Pondok Pesantren Ngalah - Afifah, Sofiatul; Saifulah, Saifulah; Marzuki, Ahmad (Literacy: Journal of Education and Social Science, 2024)
Syawir is a learning method that is characteristic of Islamic boarding schools in the form of discussions to solve a problem related to the Yellow Book. In this increasingly advanced life, there are several problems that cannot be solved alone. The method used in this research is a qualitative method, which discusses Syawir as increasing students' understanding of Islamic jurisprudence at the Ngalah Islamic Boarding School H Dormitory. Data collection techniques use interviews, observation and documentation. The research explains the various discussion methods and methods used in the discussion process and syawir learning process in H dormitory.